Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/app8071046
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Prediction Performance of Landslide Susceptibility Model Using Hybrid Machine Learning Approach of Bagging Ensemble and Logistic Model Tree

Abstract: The objective of this research is introduce a new machine learning ensemble approach that is a hybridization of Bagging ensemble (BE) and Logistic Model Trees (LMTree), named as BE-LMtree, for improving the performance of the landslide susceptibility model. The LMTree is a relatively new machine learning algorithm that was rarely explored for landslide study, whereas BE is an ensemble framework that has proven highly efficient for landslide modeling. Upper Reaches Area of Red River Basin (URRB) in Northwest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 90 publications
(134 reference statements)
0
40
0
Order By: Relevance
“…In AdaBoost model inaccuracy arises as it ignores the remaining data by concentrating on the difficult one which leads to a large range of diversity in the performance of bagging [94]. However, bagging ensemble can effectively be utilized for landslide susceptibility and has better prediction power than the conventional models [95].…”
Section: Bagging Ensemble Classifiermentioning
confidence: 99%
“…In AdaBoost model inaccuracy arises as it ignores the remaining data by concentrating on the difficult one which leads to a large range of diversity in the performance of bagging [94]. However, bagging ensemble can effectively be utilized for landslide susceptibility and has better prediction power than the conventional models [95].…”
Section: Bagging Ensemble Classifiermentioning
confidence: 99%
“…Along with the development of information technologies, remote sensing and the geographic information system (GIS) have gradually become data sources and spatial analysis platforms for LSP [6,7]. Based on remote sensing and GIS, many mathematical models have been proposed to calculate landslide susceptibility indices (LSI), such as the analytic hierarchy process [8][9][10], weight evidence method [11], information value (IV) theory [5,12], frequency ratio (FR) method [13,14], logistic regression model [7,15,16], logistic tree model [17], random tree [18,19], boosted tree [20], multi-criteria evaluation model [21], artificial neural networks (ANNs) [22][23][24], support vector machine (SVM) [25][26][27], and neuro-fuzzy method [28]. Although many models have been proposed for LSP, there is no model that is universally accepted and there is much room for improvement for these models.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that plants play an active role in the occurrence of landslides because their root systems can increase soil strength and reduce water infiltration [125][126][127]. In addition, for those factors whose AM value is less than 1, many scholars have studied their relationship with the occurrence of landslides, and these factors should not be ignored when mapping landslide susceptibility [128][129][130].…”
Section: Discussionmentioning
confidence: 99%